Thomas Aquinas on God and Evil, by Brian Davies - Siniscalchi, Glenn B (Religious Studies and Theology, 2020)
Thomas Aquinas on God and Evil, by Brian Davies. Oxford University Press, 2011. xi + 172 pp. Pb., 36.95. ISBN: 0199790906